Effect of carbon black content on the swelling of elastomers in solvent in the presence of static mechanical loading - Ch'ng, S.Y.; Andriyana, A.; Tee, Y.L.; Verron, E. (Maney Publishing, 2014)
The effect of carbon black on the mechanical properties of elastomers is of great interest because filler is one of the necessity items for manufacturing of rubber products. While fillers can be used to enhance the properties of elastomers, it is known that filler yields to significant inelastic responses such as stress-softening, hysteresis and permanent set. Moreover, under tensile loading, the filler acts as a strain amplifier in the rubber matrix resulting in a higher local strain state in the matrix as compared to the applied macroscopic strain. The study of the effect of carbon black content on the swelling characteristics of elastomeric components undergoing mechanical loading and simultaneously exposed to aggressive solvent is a prerequisite for durability analysis. The present study investigates the effect of carbon black content on the swelling of elastomers in solvent in the absence and in the presence of static tensile loadings.